Only full-sibling families evolved eusociality. - Boomsma, J; Beekman, M; Cornwallis, C; Griffin, A; Holman, L; Hughes, W; Keller, L; Oldroyd, B; Ratnieks, F (2011)
Arising from M. A. Nowak, C. E. Tarnita and E. O. Wilson 466, 1057-1062 (2010); Nowak et al. reply. The paper by Nowak et al. has the evolution of eusociality as its title, but it is mostly about something else. It argues against inclusive fitness theory and offers an alternative modelling approach that is claimed to be more fundamental and general, but which, we believe, has no practical biological meaning for the evolution of eusociality. Nowak et al. overlook the robust empirical observation that eusociality has only arisen in clades where mothers are associated with their full-sibling offspring; that is, in families where the average relatedness of offspring to siblings is as high as to their own offspring, independent of population structure or ploidy. We believe that this omission makes the paper largely irrelevant for understanding the evolution of eusociality.